ASAP-GxNet project in Burkina Faso: fulfil country capacity gaps to ensure efficient utilisation of GeneXpert instruments in tuberculosis care and cascade. Issue 1 (1st February 2019) - Alagna, Riccardo; Sawadogo, Tinnoga Lèon; Combary, Adjima; Diandé, Souba; Cirillo, Daniela Maria
In the European Respiratory Journal, Albert et al. [1] reviewed the lessons learnt from the global roll-out of Xpert MTB/RIF (Cepheid, Sunnyvale, CA, USA) highlighting the need, among others, to build country capacity to ensure an impactful introduction of new diagnostic technologies. Improving availability, accessibility and quality of national GeneXpert networks through ASAP-GxNet http://ow.ly/umaZ30mGRpE